DEVELOPMENT OF A SOLAR TRACKING SYSTEM BASED ON INTERNET OF THINGS (IOT) TECHNOLOGY - Kuttybay Н.; Amanzhol А.А.; Koshkarbay Н. Ж.; Zholamanov Б.Н.; Seitzhanova А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
Remote monitoring and control of power generation systems is an important challenge in the field of renewable energy. Effective remote monitoring allows to quickly identify faults, diagnose problems and take action to prevent serious problems, ultimately saving time and resources. This paper presents a solar energy monitoring system based on Internet of Things (IoT) technology. IoT devices are connected to sensors, allowing system parameters to be monitored in real time from anywhere in the world via an accessible network. Electronic control units have been developed, the design of the system has been described, and an algorithm for its operation has been proposed. The conducted studies are accompanied by graphical results of the operation of a photovoltaic system controlled by IoT technology. The data obtained confirm the stable and efficient operation of the developed system without identified errors. The proposed system is easy to implement, which makes it promising for wide application in the field of solar energy.